Recapitulating Trafficking of Nucleosides Into the Active Site of Polymerases of RNA Viruses: The Challenge and the Prize - Boulard, Yves; Bressanelli, Stéphane (Frontiers in Medical Technology, 2021)
Nucleoside analogs are very effective antiviral agents with currently over 25 compounds approved for the therapy of viral infections. Still, their successful use against RNA viruses is very recent, despite RNA viruses comprising some of the most damaging human pathogens (e.g. Coronaviruses, Influenza viruses, or Flaviviridae such as dengue, Zika and hepatitis C viruses). The breakthrough came in 2013-2014, when the nucleoside analog Sofosbuvir became one of the cornerstones of current curative treatments for hepatitis C virus (HCV). An analog designed on the same principles, Remdesivir, has been the first approved compound against SARS-CoV-2, the coronavirus that causes the current COVID-19 pandemic. Both of these nucleoside analogs target the RNA-dependent RNA polymerase (RdRp) (NS5B for HCV, nsp12 for SARS-CoV-2). RdRps of RNA viruses display a peculiar elaboration of the classical polymerase architecture that leads to their active site being caged. Thus triphosphate nucleosides and their analogs must access this active site in several steps along a narrow and dynamic tunnel. This makes straightforward computational approaches unsuitable for getting atomic-level details of this process. Here we give an account of ribose-modified nucleoside analogs as inhibitors of viral RdRps and of why taking into account the dynamics of these polymerases is necessary to understand nucleotide selection by RdRps. As a case study we use a computational protocol we recently described to examine the approach of the NTP tunnel of HCV NS5B by cellular metabolites of Sofosbuvir. We find major differences with natural nucleotides even at this early stage of entry.